Padina boergesenii mediated synthesis of Se-ZnO bimetallic nanoparticles for effective anticancer activity - Thirupathi, Balaji; Pongen, Yimtar Lanutoshi; Kaveriyappan, Govindarajan Rasiravathanahalli; Dara, Pavan Kumar; Rathinasamy, Suresh; Vinayagam, Saranya; Sundaram, Thanigaivel; Hyun, Baek Kwang; Durairaj, Thirumurugan; Sekar, Suresh Kumar Rajamani (Frontiers in Microbiology, 2024)
The potential of Selenium-Zinc oxide nanoparticles is of great interest due to the biocompatibility and low toxicity aspects of selenium combined with the cost-effectiveness and sustainability of zinc metal. The present study focuses on synthesizing Se-ZnO bimetallic nanoparticles from an aqueous algal extract of brown algae Padina boergesenii. Characterization studies of the synthesized Se-ZnO NPs were done using UV, FTIR, SEM-EDS and HRTEM for confirmation. The UV gave an absorbance peak at 342 and 370 nm, and the FTIR showed functional groups involved in synthesizing Se-ZnO NPs. The presence of bioactive compounds contributed to the stability of the nanoparticles and acted as capping properties. The TEM micrographs indicated the crystalline nature and confirmed the size of the Se-ZnO NPs to be at an average size of 26.14 nm. Anticancer efficacy against the MCF-7 breast and HepG2 (hepatoblastoma) cell lines were also demonstrated, attaining an IC50 value of 67.9 µg and 74.9 µg/ml respectively, which caused 50% cell death. This work aims to highlight an effective method for delivering bioactive compounds extracted from brown algae and emphasize its future therapeutic prospects.